Determination of Trace Zinc in Water by Flame Atomic Absorption Spectrometry After Preconcentration by Modified Organobentonite with 1-(2-Pyridylazo)-2-naphthol - Wang, Ying; Jun Ren, Guang; Zhang, Dong (Asian Journal of Chemistry, 2014)
A new solid-phase extraction method is described for the determination of traces of zinc in water samples by flame atomic absorption spectrophotometry. The method is based on sorption of zinc ion on the 1-(2-pyridylazo)-2-naphthol modified organobentonite (PAN-O-bentonite). And the possible parameters influencing the enrichment and separation were optimized. In the medium of pH 6, the adsorption time was 0.5 h and capacity of adsorption was 3.8 mg/g. The zinc ion adsorbed on the sorbent could be completely eluated by using 5 mL of 1 g/L of EDTA solution. And a novel method for the determination of trace zinc in water by flame atomic absorption spectrometry after preconcentration with PAN-O-bentonite was established. The enrichment factor was more than 100. Under the optimal solid-phase extraction conditions, the method detection limit was 0.031 ug/L with preconcentrated for 100 times. The established method has been successfully applied to analyze well water and tap water sample, the RSD (n = 6) within 2.71 %. The recoveries were in the range of 93.65 to 101.7 %. Compared with other solid phase extraction agent, this method has high sensitivity, better selectivity and lower cost.